ESTRUS INDUCTION AND FERTILITY RESPONSE IN POSTPARTUM ANESTRUS GIR COWS - RAMAKRISHNAN, AMMU; DHAMI, A J; NAIKOO, M; PARMAR, B C; DIVEKAR, B S (The Indian Journal of Animal Reproduction, 2023)
The study was aimed at induction/synchronization of estrus in suckler postpartum anoestrus/ suboestrus Gir cows (n=18) of an organized farm . The anoestrus/suboestrus cows were divided into 3 equal groups each of 6 animals, and a group of 6 normal cyclic cows was kept as control. Three standard synchronization protocols initiated around day 90 to 92 postpartum were CIDR, Ovsynch, and Cosynch, considering the day offirst GnRH injection or CIDR insertion as day 0. The animals were bred by fixed-time Al (FTAI). Pregnancy was confirmed per rectum on day 45 post-Al. Plasma progesterone was estimated by RIA on day O (day offirst treatment), 7 (day of PG injection), 9/10 (day of estrus/Al) and on day 10, 20, 30 and 40 post-Al. The estrus induction response as noted by uterine tone and mucus discharge was 100% in all 3 groups, but the behavioural signs were observed in 83.33, 83.33 and 100.00 % of cows under CIDR, Ovsynch and Co-synch protocols, respectively. The conception rates at induced estrus (FTAI) in CIDR, Ovsynch and Cosynch protocol were 50.00, 50.00 and 33.33 %, respectively. The corresponding overall conception rates of 2 cycles post-treatment were 83.33 (5/6), 66.66 (4/6), and 83.33 (5/ 6) %. In control group, the first service and overall conception rates were 33.33 and 66.66 (4/6) %, respectively. The results were the best with CIDR, followed by Cosynch and Ovsynch protocol. The plasma progesterone (ng/ ml) concentrations were significantly (P<0.05) higher on day 7 in CIDR (6 .65±2.43 ng/ml), Ovsynch (3.51 ng/ml) and Cosynch (6.27±0.92 ng/ml) protocols as compared to the corresponding values obtained on day O and 9/10 (Al) for the same protocols. However, the progesterone values on day 10, 20, 30 and 40 post-Al did not differ significantly between these groups and even from control group. Mean(± SE) values of plasma progesterone (ng/ ml) on day 20 and 30 post-Al were higher (P<0.05) in conceived cows than the non-conceived cows. These results suggest that use of CIDR and Cosynch protocols may serve as an excellent tool for induction/synchronization of estrus and improvement of conception rate in postpartum anestrus/subestrus Gir cows.